ANALYSIS OF GREEN BANKING, DIGITAL INNOVATION, AND CORPORATE SOCIAL RESPONSIBILITY TOWARDS SUSTAINABILITY PERFORMANCE OF SHARIA WITH CUSTOMER SATISFACTION AS A MEDIATION VARIABLE - Maritsa Cepti Andini; Muhammad Iqbal Fasa (Madani Syari'ah: Jurnal Pemikiran Perbankan Syariah, 2026)
This study aims to analyze the influence of Green Banking, Digital Innovation, and Corporate Social Responsibility (CSR) on the Sustainability Performance of Islamic banking, with Customer Satisfaction as a mediating variable. This research adopts a Systematic Literature Review (SLR) approach by analyzing 29 relevant studies published between 2020 and 2025. Data sources were obtained from reputable international journals indexed in academic database such as Scopus and Google Scholar. The findings indicate that green banking, digital innovation, and CSR each have a significant positive effect on the sustainability performance of islamic banks. Furthermore, customer satisfaction was found to mediate the relationship between these three variables and sustainability performance. This study contributes strategically to the development of islamic banking oriented toward sustainability, digital innovation, and social responsibility